Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di Era Teknologi Pendidikan - Payong, Yohanes Laga; Bafadal, Ibrahim; S Sunarni (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to analyze the strategies used by school principals to improve teacher performance in the era of educational technology. The research methods employed included interviews and surveys with school principals and teachers in several schools. The findings indicate that effective strategies involve adequate technology training and support. The implications of this research suggest that school principals play a crucial role in facilitating the integration of educational technology in schools.